Analisis Praktik Akuntansi pada Tingkat Keluarga, Masyarakat dan Bisnis di Indonesia - M. Masrukhan; Sinta Nurhaliza; Nur Aminah; Anggy Cindy Agustine (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Accounting makes a significant contribution in organizing finances at the family, community and business levels. The literature review method was used in this research to analyze accounting practices in Indonesia, by collecting secondary data from various sources. The research revealed that in the family sphere, accounting plays an important role in helping millennial couples manage their finances and achieve their financial targets. At the community level, accounting ensures transparency and accountability in the management of social funds such as those allocated to mosques. In the business world, accounting practices involve using codes of conduct, SAKs, and accounting software to ensure financial statements remain accurate. This reflects the variety of accounting practices tailored to the needs and characteristics at the family, community and business levels.